Integration of character values into PJOK learning modules in junior high schools: a literature review - Nadya Putri Adha; Wilda Welis; Zulbahri Zulbahri; Sri Gusti Handayani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study systematically reviews literature on integrating character values into junior high school Physical Education, Sports, and Health (PJOK) modules, addressing gaps between policy ideals and classroom practice. Using studies published from 2018 to 2025 across Google Scholar, ERIC, and ScienceDirect, empirical research was selected based on relevance, methodological rigor, and focus on character-based learning. Findings indicate that modules combining direct, indirect, and reflective approaches effectively foster cooperation, discipline, responsibility, and sportsmanship, particularly when supported by structured activities, guided reflection, and valid assessment tools. Core components such as integrated objectives, value-based activities, reflection sheets, and teacher guides enhance value internalization. This review highlights the need for contextually adapted modules, systematic evaluation, and teacher facilitation, providing an evidence-based foundation for designing PJOK modules that promote holistic character development in junior high school students.